PSYCHOLOGICAL ASPECTS OF PERSONNEL MANAGEMENT IN THE TRANSFORMATION OF COMPETENCES - Kokueva , Zh. M.; Yatsenko, V.V. (Modern Psychology, 2019)
The problem of transformation of personnel competencies caused by the automation effect is considered. Given the list of professions of the digital economy, referred to in various sources. Analyzed the competence of workers who will be in demand in the world economy in the coming years. Psychological aspects of personnel management in the periods of transformation of the companies connected with automation of both production, and business processes are investigated. It is shown that the acquisition of new competencies by employees within the organization depends primarily on the personal qualities of the staff, the severity of the degree of innovative behavior, and often their formation does not keep pace with the pace of reform of the organization. Measures are proposed to reduce the time of adaptation of employees to new working conditions in the digital world.
Keywords: information technologies, personal qualities, competences, psychological aspects, transformation of competences, personnel management, digital environment.